Oleg Yuriyovych Yaremchenko - KhRCHUAOT, Staff (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
On January 3, 2019, the head of the orthopedic and traumatology department of the Kherson Regional Clinical Hospital died prematurely from the insidious illness, the Honored Doctor of Ukraine, Yaremchenko Oleg Yuriyovych.